A Structured Phase Change Material with Controllable Thermoconductive Highways Enables Unparalleled Electricity via Solar‐Thermal‐Electric Conversion. (27th October 2021) - Zhang, Yongzheng; Wu, Kai; Fu, Qiang
Abstract: A solar thermoelectric generator (STEG) that harvests solar energy and converts it into electricity based on the fundamentals of the Seebeck effect is a promising alternative to photovoltaic technologies. The combination of a phase change material (PCM) with STEG further enables stable and durable energy output despite the variations of solar radiation flux. However, the widespread promotion of STEG is still impeded by its restricted output electricity (<50 W m −2 ), attributed to the undesirable thermal management in PCMs. Herein, an ingenious phase change composite, with the typical conformation of circular truncated cone and embedded with the actinomorphic arrangement of polybenzobisoxazole fibers, is tailored by a mold processing strategy. The fibrous crystals in organic fibers offer temperature‐resistance thermal highways during the charging/discharging processes, while their actinomorphic configuration facilitates a controllable thermo‐conductive behavior. These structural features render concentrated thermal energy to be efficiently stored in the PCM and maximally discharged into the thermoelectric system. A record‐breaking power density as high as 198.70 W m −2 can be achieved in this powerful STEG via real‐environment solar‐thermal‐electric conversion, a value comparable to that of some commercial photovoltaic devices. This work opens up opportunities for durable and giant electricity supply from clean solar energy during real‐time STEG applications. Abstract : A thermo‐conductive and high temperature‐stable phase change composite is fabricated by tailoring continuous polybenzobisoxazole fibers into the actinomorphic conformation for applications of solar‐thermal‐electric conversion. Attributed to the multi‐directional thermal highways to allow a remarkable charging/discharging performance, this strategy enables a solar thermoelectric generator to yield durable and unparalleled electricity reaching 198.70 W m −2, on par with some commercial photovoltaic solar panels.